Mammoth Books presents That Haunted Feeling : Six short stories by Barbara Roden, Reggie Oliver & M.R. James, Chris Bell, Richard Christian Matheson, John Gaskin and Michael Kelly /: Six short stories by Barbara Roden, Reggie Oliver & M.R. James, Chris Bell, Richard Christian Matheson, John Gaskin and Michael Kelly. (2012) - Roden, Barbara; Bell, Chris; Gaskin, John; James, M.R; Kelly, Michael; Oliver, Reggie; Matheson, Richard Christian
No abstract available